Structure-directed formation of the dative/covalent bonds in complexes with C70piperidine - Lo, Rabindranath; Lamanec, Maximilián; Wang, Weizhou; Manna, Debashree; Bakandritsos, Aristides; Dračínský, Martin; Zbořil, Radek; Nachtigallová, Dana; Hobza, Pavel (Physical chemistry chemical physics, 2021)
The combined experimental-computational study has been performed to investigate the complexes formed between C70 carbon allotrope and piperidine. The results of FT-IR, H-NMR, and C-NMR measurements, together with the calculations based on the DFT approach and molecular dynamics simulations, prove the existence of dative/covalent bonding in C70piperidine complexes. The dative bond forms not only at the region of five- and six-membered rings, observed previously with C60, but also at the region formed of six-membered rings. The structure, i.e., nonplanarity, explains the observed dative bond formation. New findings on the character of interaction of secondary amines with C70 bring new aspects for the rational design of modified fullerenes and their applications in electrocatalysis, spintronics, and energy storage.